DETERMINANT FACTOR ANALYSIS ON COMMUNITY RURAL TOURISM IN INDONESIA - Ika Sartika; Ela Lesmanawaty Wargadinata (Sosiohumaniora, 2020)
Mostly the tourist destination in Indonesia found in rural areas and belongs to the local community, who lives with limitations in terms of economy, low infrastructure accessibility, and lack of ability to manage natural resources. The study tries to portray and identify the local context of community-based tourism concepts through academic perspectives. It intended to identify the success factors of community-based tourism management for rural tourism objects in Indonesia. It conducted in five water tourism objects from five different regions, are Umbul Ponggok, Situ Panjalu, Situ Cibulan, Kola Lagundih, and Srigethuk. The research used a quantitative approach with discriminant analysis, data collected from 221 respondents through a questionnaire. The study shows that from the six predictors is that the leadership came as the main factor driving success in its implementation. Leadership plays an important role in grass root tourism management since it conceives to a traditional community. Accordingly, the traditional entities may cultural, socio-economic, structural-administration aspects are, in practice, intertwined.